Overfishing criminal threat - Uljanov Sergej (Crimen (Beograd), 2020)
Controversial nature of environmental crime and its modi operandi made the author to direct his attention to the problem of overfishing with its intricate phenomenological structure being reflection of complex environmental criminal activities. This work is backboned by paradox of environmental crime general presence followed by its drastic essence and "default low profile" being illustrated by the author's analyzing of overfishing criminal threat. Methodologically, right after initial general overview, the author introduces us to the devastating mosaic of environmental crime and its key segments, just like to its relations with other types of criminal activities. Subsequently, focus of the article shifts from targeting environmental crime to overfishing, as one of the almost daily and most frequent criminal activities and a factor in the devastation of fish stocks with unforeseeable consequences to the detriment of both nature and man. Besides determining the phenomenon of overfishing, the author puts forward typology of criminal activities as inevitable fragments of overfishing conceptual totality. Particular section of the paper is addressed by the author to the specific links among overfishing modi operandi and the whole range of various illicit activities. This is exact section set by the author to confirm his claim about actively presented conditional correlation among close phenomena ranged differently, in relation to some other phenomena likely linked to them. In nuce, if broader term is connected to other particular terms, then narrower term, derived from the same phenomenological milieu, must be related to those terms, as well. As an example, the author presents ratio between environmental crime, as broader term, and overfishing, as narrower one. Finally, as conclusion, the author warns of overfishing consequences and suggests some possible ways to combat this kind of environmental crime.